2023
DOI: 10.1002/mabi.202300213
|View full text |Cite
|
Sign up to set email alerts
|

Digital Light Processing 3D Bioprinting of Gelatin‐Norbornene Hydrogel for Enhanced Vascularization

Abstract: Digital light processing (DLP) bioprinting can be used to fabricate volumetric scaffolds with intricate internal structures, such as perfusable vascular channels. The successful implementation of DLP bioprinting in tissue fabrication requires using suitable photo‐reactive bioinks. Norbornene‐based bioinks have emerged as an attractive alternative to (meth)acrylated macromers in 3D bioprinting owing to their mild and rapid reaction kinetics, high cytocompatibility for in situ cell encapsulation, and adaptabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…[69] Our group has also used DLP bioprinting to print GelNB hydrogels for the purpose of enhancing vascularization. [119] In addition to demonstrating the cytocompatibility of DLP-printed GelNB hydrogels for in situ encapsulation and vascularization of human umbilical vein endothelial cells (HUVECs), we showed that the encapsulated HUVECs formed microvascular networks with lumen structures. Furthermore, the GelNB bioink permitted both in situ conjugation and secondary photo-tethering of pro-angiogenic and pro-vasculogenic QK peptide, a biomimetic peptide derived from vascular endothelial growth factor (VEGF).…”
Section: Bioprinting and Biofabricationmentioning
confidence: 88%
“…[69] Our group has also used DLP bioprinting to print GelNB hydrogels for the purpose of enhancing vascularization. [119] In addition to demonstrating the cytocompatibility of DLP-printed GelNB hydrogels for in situ encapsulation and vascularization of human umbilical vein endothelial cells (HUVECs), we showed that the encapsulated HUVECs formed microvascular networks with lumen structures. Furthermore, the GelNB bioink permitted both in situ conjugation and secondary photo-tethering of pro-angiogenic and pro-vasculogenic QK peptide, a biomimetic peptide derived from vascular endothelial growth factor (VEGF).…”
Section: Bioprinting and Biofabricationmentioning
confidence: 88%
“…Van Thuy Duong et al reported that they applied the thiol-norbornene cross-linked GelNB hydrogel designed and synthesized by them for encapsulating cells for vascular formation. 47 The special hydrogel has several advantages such as lower initial stiffness ( G ′ ∼ 100–4000 Pa) for better cell viability, physiological status perfusable channels and conjugation of various angiogenic peptides to improve vascularization.…”
Section: The Development Working Principles and Applications Of 3d Bi...mentioning
confidence: 99%